Expression of the gene encoding the 17-kilodalton antigen from Rickettsia rickettsii: transcription and posttranslational modification. - Anderson, B E (1988)
Recently, we reported the molecular cloning and nucleotide sequence analysis of a gene from Rickettsia rickettsii that codes for a 17-kilodalton antigen (17K antigen) and is preceded by sequences closely resembling the -10 and -35 consensus sequences for recognition by Escherichia coli RNA polymerase (Anderson et al., J. Bacteriol. 169:2385-2390, 1987). Experiments described in this report indicate that the start sites for initiating transcription of the 17K antigen gene are identical in the E. coli clone and in intact R. rickettsii. In each case, initiation was shown to begin 9 bases downstream of the presumed Pribnow box sequence (TATACT). A 169-base-pair fragment containing the promoter sequence initiated transcription in both directions when cloned into an E. coli promoter probe vector. The rickettsial fragment was found to contain sequences identical to the -10 region (but not the -35 region) of the E. coli promoter consensus sequence directed away from the 17K antigen gene. The amino-terminal portion (residues 17 to 20) of the deduced amino acid sequence for the 17K antigen contained the tetrapeptide Leu-Gln-Ala-Cys, a sequence that conforms favorably to those described for lipid modification and cleavage by lipoprotein signal peptidase II. The 17K antigen produced by the E. coli clone was shown to be labeled with [3H]palmitate and [3H]glycerol, indicative of lipid modification. In vitro mutagenesis designed to alter the cysteine at residue 20 to a glycine abolished incorporation of [3H]palmitate, suggesting that posttranslational modification occurs via a mechanism similar to that described for other gram-negative bacterial lipoproteins.